Clinical researchRopivacaine plasma concentrations after thoracic epidural anaesthesia - Kostopanagiotou, Georgia; Matsota, Paraskevi; Batistaki, Chrysanthi; Souliotis, Zoi; Pandazi, Ageliki; Markantonis, Sophia (Archives of Medical Science, 2008)
Introduction: The pharmacokinetic profile of ropivacaine varies according to the site of administration. The aim of this study was to determine ropivacaine plasma concentrations after thoracic epidural administration in patients undergoing abdominal surgery under combined epidural – general anaesthesia. Material and methods: The study included 15 patients, aged 45-77 years, ASA I and II, scheduled for abdominal procedures, under combined epidural-general anaesthesia. Epidural was performed at T10-T11 or T11-T12 interspaces and all patients received 5 ml of ropivacaine 0.75% with fentanyl 100 µg. Blood samples were collected at 10, 40, 70, 100 and 130 min following ropivacaine administration. Determination of blood levels was achieved with high performance liquid chromatography. Results: Mean ropivacaine plasma concentrations determined at 10, 40, 70, 100 and 130 min after epidural administration showed significant intersubject variation and were found to be 0.66±0.48, 0.43±0.26, 0.47±0.34, 0.40±0.2, 0.33±0.19 µg/ml, respectively. Peak plasma concentrations occurred 10 min after administration in 10 patients, at 40 min in one patient, at 70 min in 3 patients and at 100 min in 1 patient with a mean of 0.65±0.46 µg/ml (range 0.25-1.59 µg/ml). The terminal half-life determined in 12 of the 15 patients was roughly estimated to be between 60 and 245 min (mean ± SD = 122±55 min). Conclusions: Thoracic epidural administration of 5 ml ropivacaine 0.75% achieved plasma concentrations of between 0.1-1.59 µg/ml with an elimination half-life of approximately 122±55 min.